High-Entropy Catalysts for Biomass-Derived Chemicals Valorization: Mechanisms, Applications, and Opportunities - Li, Fan; Chen, Longli; Chen, Siwei; Ma, Zhihui; Wang, Qiang; Li, Fukuan; Shen, Feng (Nano-Micro Letters, 2026)
The valorization of biomass-derived chemicals into high-value chemicals represents a crucial pathway toward a sustainable and low-carbon economy. However, the structural complexity and multifunctionality of these molecules demand catalysts capable of multisite activation and precise chemo-selectivity. High-entropy catalysts (HECs), which integrate five or more principal elements into a single phase, have recently emerged as a promising materials platform, offering tunable active sites, enhanced stability, and unique synergistic effects. This review provides a comprehensive and up‑to‑date overview of recent advances in HECs for the valorization of biomass‑derived chemicals. We first clarify the definition of high‑entropy materials and elucidate the relationships between the four core effects and catalytic performance. Subsequently, we systematically outline the key elements frequently incorporated in HECs, emphasizing their roles in modulating active sites and electronic structures. Design strategies, including component modulation, morphology/size regulation, defect engineering, and heterostructure construction, are discussed with a focus on synergistic mechanisms governing biomass conversion. The applications of HECs in major valorization reactions, including oxidation of 5-hydroxymethylfurfural (HMF), hydrogenation of HMF and furfural (FF), oxidative condensation of FF, depolymerization of lignin, and conversion of glucose and glycerol are detailed, highlighting clear correlations between catalyst structure and catalytic efficacy. Finally, we identify prevailing challenges and outline future research directions aimed at the rational design of next-generation HECs for efficient and selective biomass upgrading. This work aims to serve as a foundational reference and stimulate further innovation in the application of HECs in biorefinery and green chemistry. Highlights: 1 This review comprehensively summarizes the latest advances of high entropy catalysts (HECs) in biomass derived chemicals valorization, covering their core effects, elemental composition principles, structural design strategies, and typical application reactions. 2 The unique advantages of HECs and their structure–activity relationships in biomass conversion are systematically clarified. 3 Future directions of HECs for biomass-derived chemicals valorization are outlined, including precise design via computational-experimental integration, expansion of catalyst types and reaction scope, and exploration of novel structure regulation strategies.